Thermal and antimicrobial evaluation of cotton functionalized with a chitosan–zeolite composite and microcapsules of phase‐change materials. Issue 15 (27th December 2017) - Scacchetti, Fabio A. P.; Pinto, Eugénia; Soares, Graça M. B.
ABSTRACT: Antimicrobial cotton was developed with silver zeolites (SZs). Three different application approaches for the cotton surface functionalization were followed: (1) SZ alone, (2) SZ combined with chitosan film, and (3) chitosan–zeolite (CS–SZ) composites previously synthesized by a gelation process with sodium tripolyphosphate. All finishes were applied to the textile materials through conventional pad–dry–cure processes, and the obtained results were then compared. The resulting materials were characterized with Fourier transform infrared spectroscopy, scanning electron microscopy with energy‐dispersive X‐ray spectroscopy, differential scanning calorimetry, IR thermography, and contact angle measurements, and the antimicrobial activity was evaluated. The results suggest that the application of CS–SZ should be recommended for the production of textiles with antibacterial properties because the materials showed activity against Escherichia coli, Staphylococcus aureus, Candida albicans, and Trichophyton rubrum . In addition, the finishing can be combined with the application of microcapsules of phase‐change materials to obtain textiles with thermoregulating properties. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46135. Abstract :